Thyroid Crisis and Diabetic Ketoacidosis in Uncontrolled Diabetes - Putri, Desy Puspa; Prabowo, Nurhasan Agung; Hermawati, Berty Denny (Faculty of Medicine Universitas Sebelas Maret, 2023)
Introduction: Thyroid crisis is a medical emergency that causes damage to various organs of the body so that proper diagnosis and immediate treatment are needed. Excess thyroid hormone also affects blood sugar metabolism, especially in diabetic patients. The occurrence of thyroid crisis in conjunction with diabetic ketoacidosis (DKA) is rare, and the exact pathogenesis is still being investigated. We report a case of thyroid crisis in a DKA patient.Case Presentation: A 35-year-old woman was brought by her family to the ER due to a loss of consciousness since 6 hours before admission to the hospital. The patient was said to have complained of fever, shortness of breath, palpitations since the previous day. The patient has a history of uncontrolled Type 2 Diabetes Mellitus (DM) since 5 years ago. Physical examination showed somnolence, blood pressure 120/72 mmHg, pulse rate 126 beats per minute, irregular, respiratory rate 28 breaths per minute, fast and deep breaths. Investigations showed blood sugar 320 mg/dL, uncompensated metabolic acidosis, ketonuria. The patient received DKA therapy, but her consciousness and pulse rate had not improved. TSH levels was low with an increase in fT4 levels, with the Burch-Wartofsky score supporting a thyroid crisis. The patient then received treatment for thyroid crisis and her clinical condition showed significant improvement.Conclusion: The occurrence of thyroid crisis along with DKA is a life-threatening emergency. Untreated hyperthyroid induce severe hyperglycemia and causes acute condition in both organs.